2023
DOI: 10.1097/wco.0000000000001218
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to treatment of leptomeningeal metastases

Ditte Primdahl,
Adam Cohen-Nowak,
Priya Kumthekar

Abstract: Purpose of review The incidence of leptomeningeal metastases is increasing in the setting of improved survival from systemic cancers. In more recent years, our understanding of leptomeningeal metastasis pathogenesis, how to diagnose and treat has been evolving. Recent findings Diagnosing leptomeningeal metastasis has been challenging due to the limitations of cytology and neuroimaging; However, newer techniques detecting circulating tumor cells (CTCs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Moreover, multiple trials have shown potential efficacy of targeted therapies (i.e., HER2, EGFR, ALK, BRAF, etc.). 22 As for nasopharyngeal carcinoma, it is reported that whole brain radiotherapy combined with oral capecitabine is effective in a case of LM of NPC. 21 A combination of local therapy and systemic chemotherapy might have therapeutic potential in these patients with LM.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multiple trials have shown potential efficacy of targeted therapies (i.e., HER2, EGFR, ALK, BRAF, etc.). 22 As for nasopharyngeal carcinoma, it is reported that whole brain radiotherapy combined with oral capecitabine is effective in a case of LM of NPC. 21 A combination of local therapy and systemic chemotherapy might have therapeutic potential in these patients with LM.…”
Section: Discussionmentioning
confidence: 99%